Therapeutic physical training as a means of prevention for children with frequent episodes of acute respiratory diseases - Пєшкова Ольга Володимирівна (Olga Peshkova) (Slobozhanskyi Herald of Science and Sport, 2015)
In the article the author described therapeutic physical training as a means of preventing recurrent acute respiratory diseases in sickly children. Purpose: to describe the main approaches to the appointment of medical physical training as a means of prevention of recurrent disease for children with frequent episodes of acute respiratory diseases. Material and Methods: analysis of the current literature on the researched topic. Results: the author defines the general and specific objectives of exercise therapy in sickly children, characterized by means of physical therapy appointment procedure for two periods – preparatory and trains, provides an approximate complexes of gymnastics and morning hygiene gymnastics for sickly children to training period.